Liquid based cytology: examination of its potential in a chlamydia screening programme. Issue 5 (30th September 2004) - Hopwood, J; Mallinson, H; Hodgson, E; Hull, L
Abstract : Objective: To assess the feasibility of testing for chlamydia directly on a single liquid based specimen (ThinPrep test) collected for cervical screening. Method: Cervical smears were taken using a Cervex spatula and rinsed in the liquid based cytology collection vial. Following this, the conventional sample for chlamydia testing was taken from the endocervix using an Abbott Collection kit. Cytological specimens were prepared using an automated slide processor. Residual cellular material and the conventional samples were sent to the laboratory where both were tested for chlamydia by ligase chain reaction (LCR). The manufacturer's protocol for LCR urine testing was modified to substitute 1 ml of PreservCyt suspension. Results: 581 women had both swab and cytology suspension tested for Chlamydia trachomatis with LCR. There were 19 concordant positive and 562 concordant negative reports. The stability of chlamydia in the cytology suspension was maintained for at least 5 months. Conclusion: The findings lead us to conclude that samples collected for liquid based cytology using the ThinPrep test collection vial provide a potential platform for chlamydia screening, though the study established several issues to be addressed to make this a practical proposition.